Answer:
D
Step-by-step explanation:
Answer:
Explanation:
fg(x) = (x+2)(3x^2 - 1)
= 3x^3 - x + 6x^2 - 2
= 3x^3 + 6x^2 - x - 2
gf(x) = (3x^2 - 1)(x + 2)
= 3x^3 + 6x^2 - x - 2
As you can see:
fg(x) = gf(x)
3x^3 + 6x^2 - x - 2 = 3x^3 + 6x^2 - x - 2
Answer:
x = 17 and y = 8
Step-by-step explanation:
Since (6x + 3) and (8x - 31) are alternate interior angles, they are congruent.
Therefore, you can set them equal to each other and solve for x.
8x - 31 = 6x + 3
Combine like terms
2x = 34
Divide both sides by two
x = 17
Since (5y + 35) and (6x + 3) are consecutive interior angles, they add up to 180. Plug in 17 for x.
(5y + 35) + (6(17) + 3) = 180
Add like terms
5y + 140 = 180
5y = 40
y = 8
Answer:
-38.4
Step-by-step explanation:
Multiply both sides by 6 to get rid of the /6 then you would get z alone